1961
DOI: 10.1111/j.1365-2621.1961.tb00781.x
|View full text |Cite
|
Sign up to set email alerts
|

Pectic Substances of Valencia Oranges at Different Stages of Maturitya

Abstract: Seasonal changes in concentrations of pcctic substances of the peel and pulp were followed by determining the total-and water-soluble pectic substances as anhydrogalacturonic acid during growth and development under normal conditions. With the rapid development of fruit growth in the early part of the season, a tremendous initial increase occurred in the total-and water-soluble pectic materials followed 'by a gradual decrease through the remainder of the season. The percentage methylation of the pectic substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
1

Year Published

1964
1964
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 3 publications
2
4
1
Order By: Relevance
“…In 2012, pectin levels were generally consistent over the season, although there was an increase of about 20% from February to May, and juice from the later harvested fruit had wide variability (Table 1). The results are in contrast to Sinclair and Jolliffe [48] and Rouse et al [49] who observed that in maturing oranges, total pectin and water-soluble pectic substances decreased in the peel and pulp, in both California and Florida “Valencia” fruit. However, Rouse and Moore [50] reported that pectin content in “Valencia” OJ increased in the 1973 season, but decreased in 1974.…”
Section: Resultscontrasting
confidence: 98%
“…In 2012, pectin levels were generally consistent over the season, although there was an increase of about 20% from February to May, and juice from the later harvested fruit had wide variability (Table 1). The results are in contrast to Sinclair and Jolliffe [48] and Rouse et al [49] who observed that in maturing oranges, total pectin and water-soluble pectic substances decreased in the peel and pulp, in both California and Florida “Valencia” fruit. However, Rouse and Moore [50] reported that pectin content in “Valencia” OJ increased in the 1973 season, but decreased in 1974.…”
Section: Resultscontrasting
confidence: 98%
“…However, a previous study showed that the MC of pectin from orange peel increased rapidly in early season and remained constant until late season. 39 Our results also showed that the extent of increase in pectin MC in segment membrane and albedo is higher than in¯avedo. Furthermore, the MC of pectin in segment membrane is slightly higher than in¯avedo during late season.…”
Section: Methoxyl Contentsupporting
confidence: 67%
“…With the exception of orange cerning the structure of the cell wall and its relationship to peel, which was found to increase from 62 to 80% methylation tissue firmness. The major neutral sugars in the cell wall polyduring fruit development (Sinclair and Jolliffe, 1961), pectin esterification generally remains constant as in apples (Woodmansee et al, 1959;DeVries et al, 1981) or decreases, as occurs in avocado and pear (McCready andMcComb, 1954), tomato (Woodmansee et al, 1959), peaches (Sterling and Kalb, 1959), and cherries (Davignon, 1961). The positive correlation between the fresh weight concentration of cell wall sugars and cucumber firmness suggested that, at least as a first approximation, firmness could be predicted by the total cell wall sugar content.…”
Section: Discussionmentioning
confidence: 95%
“…Gross and Sams (1984) measured the noncellulosic neutral sugars at three developmental stages for 15 fruits, including cucumbers. Investigations of cell wall changes throughout fruit development have been done for Valencia oranges (Sinclair and Jolliffe, 1961) and strawberries (Knee et al, 1977).…”
Section: Introductionmentioning
confidence: 99%